2012
DOI: 10.1152/ajplung.00221.2011
|View full text |Cite
|
Sign up to set email alerts
|

The role of low-level lactate production in airway inflammation in asthma

Abstract: Warburg and coworkers (Warburg O, Posener K, Negelein E. Z Biochem 152: 319, 1924) first reported that cancerous cells switch glucose metabolism from oxidative phosphorylation to aerobic glycolysis, and that this switch is important for their proliferation. Nothing is known about aerobic glycolysis in T cells from asthma. The objective was to study aerobic glycolysis in human asthma and the role of this metabolic pathway in airway hyperreactivity and inflammation in a mouse model of asthma. Human peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 35 publications
6
102
1
Order By: Relevance
“…This is in contrast with another study, which has shown that DCA inhibits T-cell clonal expansion (28). However, in that study T cells were murine, activated with anti-CD3/CD28 antibodies and the supra-pharmacological concentration of 20 mM DCA was used (28). We used MLRs, which is a model of alloimmunity (27), and DCA at a concentration of 1 mM, which is close to the blood concentrations of this drug when used for the treatment of hereditary lactic acidosis (19).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with another study, which has shown that DCA inhibits T-cell clonal expansion (28). However, in that study T cells were murine, activated with anti-CD3/CD28 antibodies and the supra-pharmacological concentration of 20 mM DCA was used (28). We used MLRs, which is a model of alloimmunity (27), and DCA at a concentration of 1 mM, which is close to the blood concentrations of this drug when used for the treatment of hereditary lactic acidosis (19).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with another study, which has shown that DCA inhibits T-cell clonal expansion (28). However, in that study T cells were murine, activated with anti-CD3/CD28 antibodies and the supra-pharmacological concentration of 20 mM DCA was used (28).…”
Section: Discussionmentioning
confidence: 83%
“…DCA has also been shown to reduce proinflammatory cytokine production and promote FoxP3 expression in vitro and in several in vivo inflammatory models (19)(20)(21), although the mechanisms involved have not been established.…”
Section: T Cells Undergo Metabolic Reprogramming Toward a Glycolytic mentioning
confidence: 99%
“…While DCA has been previously shown to suppress inflammation in arthritis, asthma, and alloreactivity (19)(20)(21), the specific effect on the differentiated CD4 + T cell subsets has not been examined in vivo. We therefore tested the ability of DCA to suppress the Th17-mediated inflammatory diseases.…”
Section: Inhibition Of Pdhk In Vivo Differentially Affects Th17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation